2010
DOI: 10.1186/1472-684x-9-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying obstacles to participation in a questionnaire survey on widowers' grief

Abstract: BackgroundThe aim of this study was to determine if Icelandic widowers might foresee obstacles to responding to a questionnaire on bereavement. Also, we sought to compare the proportion of men reporting obstacles in a telephone interview to the actual response rate in the questionnaire survey.MethodsThe study was part of a nation-wide survey of widowers who lost their wives in 1999, 2000, and 2001. This included all widowers born in Iceland 1924-1969 (aged 30-75 years) who were alive, and residing in Iceland a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A recently published study from a nationwide population-based survey of Icelandic widowers reported similar indications of resistance to expressing emotional concerns. The study showed that, in spite of a strong interest in the subject, a majority of widowers identified emotional obstacles to participation in a questionnaire survey on bereavement [ 73 ]. Previous findings from a population-based study in Sweden demonstrated a significantly lower prevalence of “emotional isolation” in middle aged and elderly women [ 74 ] compared with men [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study from a nationwide population-based survey of Icelandic widowers reported similar indications of resistance to expressing emotional concerns. The study showed that, in spite of a strong interest in the subject, a majority of widowers identified emotional obstacles to participation in a questionnaire survey on bereavement [ 73 ]. Previous findings from a population-based study in Sweden demonstrated a significantly lower prevalence of “emotional isolation” in middle aged and elderly women [ 74 ] compared with men [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first is that the study is based on a convenience sample volunteering to participate. In addition, the sample consisted largely of women, both because of a high presentation of women with breast cancer in the clinics where data collection took place, and possibly also because men have been found to be somewhat reluctant to participate in similar questionnaire surveys [36]. Third, the cut‐off criterion used for both HADS and GHQ‐30 is based on non‐Icelandic samples [21, 24] although cut‐off scores for both GHQ‐30 [25] and HADS [37] have been supported in Icelandic studies.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was an extension of an epidemiological nation-wide study assessing widowers' psychological and physiological well-being and comparing them to a group of age-matched married men. Parts of that study have been previously published [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study is the first nationwide study of widowers' mortality in Iceland. It is an extension of a study on widowers assessing widowers' psychological and physiological well-being and comparing them with an age-matched control group of married men over a period of 6 to 9 years [ 32 ].…”
Section: Introductionmentioning
confidence: 99%